"People just don't look at you the same way": Public stigma, private suffering and unmet social support needs among mothers who use drugs in the aftermath of child removal. (February 2018) - Kenny, Kathleen S.; Barrington, Clare
Abstract: Reduced social support among parents is a well-established risk factor for child removal by child protective services. There has been relatively little attention, however, to mothers' social networks following child removal, including how stigma and additional strain of living apart from children may influence mothers' social ties. Foregrounding the rarely heard perspectives of mothers who use drugs, a group disproportionately intervened upon by child protective services, this study examines social relationships and social support among mothers in the aftermath of child removal. We conducted in-depth interviews with 19 women who use drugs and conducted thematic analysis to examine social relationships and patterns of social support. Women reported severely disadvantaged social networks following child removal, with network ties commonly cited as providing low support, most often attributed to poverty-related adversities, lack of acknowledgment of the traumatic nature of women's losses, and pronounced stigmatization. Findings highlight how unmet social support needs and stigma can act to deepen social blame and marginalization of mothers following child removal, impeding efforts toward family reunification and foreclosing other life opportunities. More mutually supportive, peer-to-peer spaces are needed to provide support to parents currently involved in the system and to challenge processes of stigmatization. Highlights: We examined social support networks of women who use drugs following child removal. Women reported severely disadvantaged social support networks following child removal. Stigma delegitimized traumatic nature of women's losses and reinforced social blame. Peer-led initiatives to support mothers and foster social resilience are needed for this population.